2021
DOI: 10.1136/bmjopen-2020-047216
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of anti-SARS-CoV-2 IgG among healthcare workers of a large university hospital in Milan, Lombardy, Italy: a cross-sectional study

Abstract: ObjectivesTo assess the seroprevalence of anti-SARS-CoV-2 IgG among health careworkers (HCWs) in our university hospital and verify the risk of acquiring the infection according to work area.DesignCross-sectional study.SettingMonocentric, Italian, third-level university hospital.ParticipantsAll the employees of the hospital on a voluntary base, for a total of 4055 participants among 4572 HCWs (88.7%).Primary and secondary outcome measuresNumber of anti-SARS-CoV-2 positive serology according to working area. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 28 publications
14
33
0
Order By: Relevance
“…Regarding the highest titres observed among those who presented symptoms, this parallel similar observations that our and other groups have made also for anti-N antibodies, elicited only by natural infection [ 10 ]. Among the other, Legros et al demonstrated how neutralizing antibodies (nAb) titres correlated strongly with disease severity and with anti-spike IgG levels, with patients from intensive care units exhibiting high nAb titres whereas asymptomatic or exclusive outpatient-care patients had no or low nAbs [ 11 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Regarding the highest titres observed among those who presented symptoms, this parallel similar observations that our and other groups have made also for anti-N antibodies, elicited only by natural infection [ 10 ]. Among the other, Legros et al demonstrated how neutralizing antibodies (nAb) titres correlated strongly with disease severity and with anti-spike IgG levels, with patients from intensive care units exhibiting high nAb titres whereas asymptomatic or exclusive outpatient-care patients had no or low nAbs [ 11 ].…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, as we previously observed for anti-N antibodies, anti-S1 antibodies titres were lower among smokers [ 10 ]. This confirm the impact of smoking on the immune system and its ability to mount an humoral response to inhaled but also injected antigens, a finding in contrast with previous evidence which suggested an influence only on inhaled antigens [ 12 ].…”
Section: Discussionsupporting
confidence: 70%
“…in Spain have discussed ageusia and anosmia as the most predictive symptoms of COVID-19 infection in their studies (13, 16). Our study showed lower percentage of seropositive HCWs showing anosmia and ageusia which could be described as variation due to subjects characteristics and geographical variations(14). We found that 34.1% of seropositive HCWs were asymptomatic until the time of investigation since the last 6 months.…”
Section: Discussionmentioning
confidence: 55%
“…Similar study performed by Lombardi Andrea et.al. in Italy revealed the Seroprevalence rate to be 7.6% (14). The higher seroprevalence in our study is corresponding with the 24.4% prevalence rate as reported by Adrian M. et.al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation